Aspectos da quebra da simetria de Lorentz e não-comutatividade em modelos com gravitação - Santos, Victor Pereira do Nascimento (2014)
In this work we will present some aspects from quantum gravity. We introduce the problem of quantum gravity and some proposals to tackle it. In particular, our investigations touch upon three general subjects: noncommutative geometry, violations of Lorentz symmetry and inflationary cosmology. In noncommutative geometry we made two proposals for possible experimental verifications: in the former we calculate the luminosity of spherically symmetric black-hole where its event horizon was modelled by a noncommutative space; in the latter we investigate the thermodynamical properties of the graphene in the presence of a magnetic field, verifying the influence of the noncommutativity. Regarding the Lorentz symmetry violation we showed its physical viability of extra-dimensional scenarios, by calculating the graviton mass in the four-dimensional effective theory. We also calculate the influence of the Lorentz symmetry breaking in the gravitational sector in four dimensions, by means of quantum corrections to the Newtonian potential. Finally, in cosmology we present a preliminar study on the measure problem, which is related to how natural the inflationary process is. We propose using the Hamiltonian formulation for evaluating the probability of inflation in a scenario where the scalar field describing the inflation is non-minimally coupled to the gravitational field, finding the the viability of this particular model when compared to observed data.